The Effect of Clay, Alumina, and Starch Composition on The Characteristics of Thermal Insulation Cylinders - Suluh, Sallolo; Bethony, Frans Robert; Simon, Christof Geraldi; Gallaran, Ferayanti Boas; Aket, Paulus; Pasampa, Enos (Jurnal Polimesin, 2025)
Efficient thermal insulation materials are crucial in improving performance, minimizing energy consumption, and maintaining safety in various industrial applications. This study examines the impact of multiple combinations of clay, alumina, and starch on the properties of thermal insulation cylinders. Five different composite samples were prepared by adjusting the percentages of clay and alumina while maintaining a consistent starch content. The samples were subjected to comprehensive tests to assess their water content, density, and porosity. Based on the findings, it was observed that as the alumina content increased, the water content and density of the composite materials decreased while their porosity increased. The sample labeled C6-A2 had the highest water content (9.19%) and density (1,087.04 kg/m³), while the sample labeled C2-A6 had the lowest water content (8.69%) and density (1,069.93 kg/m³). The range of porosity values observed was between 25.67% and 26.60%. It was observed that an increase in alumina content resulted in a corresponding increase in porosity. The findings indicate that the larger particle size and lower cohesion of alumina result in a more porous microstructure, affecting the material's overall properties. This study offers valuable insights into the composition optimization of clay, alumina, and starch to create customized composite materials suitable for various industrial applications. It focuses on achieving a delicate balance between water resistance, structural integrity, and thermal insulation